Significant Association Between Adiponutrin and Hepatocellular Carcinoma Risk. Issue 47 (November 2015) - Li, Hong-Guang; Liu, Fang-Feng; Zhu, Hua-Qiang; Zhou, Xu; Lu, Jun; Chang, Hong; Hu, Jin-Hua
Abstract : Abstract: ADPN I148M polymorphism has been consistently reported to play a role in liver-associated diseases, such as alcoholic liver disease, chronic hepatitis C, and liver fat and fibrosis in nonalcoholic fatty liver disease. This significant association was also indicated in a series of hepatocellular carcinoma (HCC) studies, where the significance may be affected due to the small sample sizes. The aim of this study was to reexamine the ADPN -HCC association by use of meta-analysis. Biweekly computer-based literature searches plus manual screening were undertaken in an effort to identify all studies that met the predefined inclusion criteria. The Mantel–Haenszel method was selected to estimate risk effects (odds ratio [OR] and 95% confidence interval [CI]). To examine reliability of the pooled risk effects, we additionally performed sensitivity analysis and publication bias tests. Ten studies (1335 HCC patients and 2927 HCC-free controls) were identified for the meta-analysis. We found significantly increased risk of HCC attributable to presence of ADPN I148M polymorphism, with the highest risk associated with the M/M genotype under the recessive model of inheritance (OR = 2.23, 95% CI = 1.87–2.67, between-study heterogeneity: P  = 0.468). The significant increase persisted in Caucasian and African when data were stratified by ethnicity. Subgroup analysis according to source of controls revealed similar risk effects. Our meta-analysis indicates that I148M polymorphism in the ADPN gene may independently contribute to the progression of HCC irrespective of the etiologies.